Preferential Homologous Chromosome Pairing in a Tetraploid Intergeneric Somatic Hybrid (Citrus reticulata + Poncirus trifoliata) Revealed by Molecular Marker Inheritance - Kamiri, Mourad; Stift, Marc; Costantino, Gilles; Dambier, Dominique; Kabbage, Tariq; Ollitrault, Patrick; Froelicher, Yann (Frontiers in Plant Science, 2018)
The creation of intergeneric somatic hybrids between Citrus and Poncirus is an efficient approach for citrus rootstock breeding, offering the possibility of combining beneficial traits from both genera into novel rootstock lineages. These somatic hybrids are also used as parents for further tetraploid sexual breeding. In order to optimize these latter breeding schemes, it is essential to develop knowledge on the mode of inheritance in the intergeneric tetraploid hybrids. We assessed the meiotic behavior of an intergeneric tetraploid somatic hybrid resulting from symmetric protoplast fusion of diploid Citrus reticulata and diploid Poncirus trifoliata. The analysis was based on the segregation patterns of 16 SSR and 9 newly developed centromeric/pericentromeric SNP markers, representing all nine linkage groups of the Citrus genetic map. We found strong but incomplete preferential pairing between homologues of the same ancestral genome. The proportion of gametes that can be explained by random meiotic chromosome associations (τ) varied significantly between chromosomes, from 0.09+/-0.02 to 0.47+/-0.09 respectively in chromosome 2 and 1. This intermediate inheritance between strict disomy and tetrasomy resulted in a high level of intergeneric heterozygosity of the diploid gametes. Whatever limited, intergeneric recombination occurred, whose observed rates, ranging from 0.09 to 0.29 respectively in chromosome 2 and 1, were significantly correlated with τ. Such inheritance is of particular interest for rootstock breeding because a large part of the multi-trait value selected at the teraploid parent level is transmitted to the progeny, while the potential for some intergeneric recombination offers opportunities for generating plants with novel allelic combinations that can be targeted by selection.